Punic black-gloss ware in Nora (south-western Sardinia, Italy): Production and provenance. (February 2019) - Maritan, Lara; Zamparo, Luca; Mazzoli, Claudio; Bonetto, Jacopo
Abstract: The present archaeometric study of the Punic black-gloss ware found at the "Roman Temple" of Nora (south-western Sardinia, Italy), dated at the end of the IV century BCE and the beginning of the II century BCE, was addressed to better define the exchanges of Punic ware, ideas and production skills within the west Mediterranean Sea. Petrographic and microstructural analyses at the scanning electron microscope (SEM) clearly indicate that the analysed pottery can be referred to two different productions, for which different base-clays were used, indicating different geological origin. On the basis of chemical composition, the black-gloss ware found at Nora can be traced back in part to the northern African area and in part to the western Sardinia coast at Tharros. None local production was identified. Moreover, on the basis of both the mineralogical composition and the microstructural features, samples produced in the northern African area and in western Sardinia definitely differ in terms of firing temperature. Therefore, on the basis of these results, a more complete scenario can be drawn on the commercial traffic active in the Western Mediterranean and in Sardinia between the end of the IV century and the first half of the II century BCE. Under a social perspective, Sardinia, thanks to its Phoenician, Punic and Italic influences, became an incubator of ideas, techniques and production knowledge that, from the interaction of the preceding cultures and their influences, gave life to many local productions, which were part of the greater phenomenon of Punic black-gloss ware in the western Mediterranean (Sardinia, Sicily, Northern Africa and the southern coasts of the Iberian Peninsula). Highlights: Archaeometric study of the Punic black-gloss ware from Nora (south-western Sardinia) Paste composition indicates two different productions. Punic black-gloss ware imported from northern African area and from Tharros. None local production was identified. Punic black-gloss from northern African was fired at higher temperature.